2015
DOI: 10.3892/mmr.2015.3454
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan oligosaccharides in combination with Agaricus blazei Murill extract reduces hepatoma formation in mice with severe combined immunodeficiency

Abstract: Chitosan and Agaricus blazei Murill (ABM) extracts possess antitumor activities. The aim of the present study was to investigate whether chitosan, ABM extract or the two in combination were effective against tumors in tumor-bearing mice. The mice were subcutaneously injected with SK-Hep 1 cells and were then were divided into the following six groups: Group 1, control group; group 2, chitosan 5 mg/kg/day; group 3, chitosan 20 mg/kg/day; group 4, ABM (246 mg/kg/day) and chitosan (5 mg/kg/day) combined; group 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Wu et al [43,44] showed that AbM extract inhibited growth of colon cancer, hepatoma and melanoma in severe combined immunodeficient (SCID) mice and increased their life span in a dose-dependent manner. The finding of AbM (combined with chitosan N-acetyl glucosamine) inhibiting hepatoma cell growth in SCID mice was confirmed later [41]. Pinto et al [45] observed that a β-glucan-rich AbM preparation reduced growth of Ehrlich tumor after intratumor injection, increased blood levels of IFNγ, CD4+ T cells and macrophages (MΦ), and reduced interleukin (IL)-10, resulting in immune cell migration to tumor and cytokine switch.…”
Section: Antitumor Effects Of Abm-preclinical Studiesmentioning
confidence: 86%
“…Wu et al [43,44] showed that AbM extract inhibited growth of colon cancer, hepatoma and melanoma in severe combined immunodeficient (SCID) mice and increased their life span in a dose-dependent manner. The finding of AbM (combined with chitosan N-acetyl glucosamine) inhibiting hepatoma cell growth in SCID mice was confirmed later [41]. Pinto et al [45] observed that a β-glucan-rich AbM preparation reduced growth of Ehrlich tumor after intratumor injection, increased blood levels of IFNγ, CD4+ T cells and macrophages (MΦ), and reduced interleukin (IL)-10, resulting in immune cell migration to tumor and cytokine switch.…”
Section: Antitumor Effects Of Abm-preclinical Studiesmentioning
confidence: 86%
“…Agaricus blazei Murill (AbM) is a nutritive mushroom origin in Brazil. It is cultivated in countries like Indonesia, Taiwan, China, Japan and Korea 7 . It is a basidiomycete generally familiar as sun mushroom.…”
Section: Discussionmentioning
confidence: 99%
“…Dosage Information/Dosage Regimen: All experimental procedures were approved by the Ethics Committee, West China School of Stomatology, Sichuan University (document number: WCHSIRB-D-2021-472). The experimental period was set to 14 days, and the dosage of ABMP was 1% (in drinking water w/v and daily intake of ABMP was 1100 mg kg -1 ) according to previous studies [32][33][34][35] and animal average daily water intake (Table S2, Supporting Information). In vitro, ABMP was administered at 5 μg mL -1 .…”
Section: Methodsmentioning
confidence: 99%